Management of primary skin cancer during a pandemic: Multidisciplinary recommendations. Issue 17 (1st June 2020) - Baumann, Brian C.; MacArthur, Kelly M.; Brewer, Jerry D.; Mendenhall, William M.; Barker, Christopher A.; Etzkorn, Jeremy R.; Jellinek, Nathaniel J.; Scott, Jeffrey F.; Gay, Hiram A.; Baumann, John C.; Manian, Farrin A.; Devlin, Phillip M.; et al.
Abstract : During the coronavirus disease 2019 (COVID‐19) pandemic, providers and patients must engage in shared decision making regarding the pros and cons of early versus delayed interventions for localized skin cancer. Patients at highest risk of COVID‐19 complications are older; are immunosuppressed; and have diabetes, cancer, or cardiopulmonary disease, with multiple comorbidities associated with worse outcomes. Physicians must weigh the patient's risk of COVID‐19 complications in the event of exposure against the risk of worse oncologic outcomes from delaying cancer therapy. Herein, the authors have summarized current data regarding the risk of COVID‐19 complications and mortality based on age and comorbidities and have reviewed the literature assessing how treatment delays affect oncologic outcomes. They also have provided multidisciplinary recommendations regarding the timing of local therapy for early‐stage skin cancers during this pandemic with input from experts at 11 different institutions. For patients with Merkel cell carcinoma, the authors recommend prioritizing treatment, but a short delay can be considered for patients with favorable T1 disease who are at higher risk of COVID‐19 complications. For patients with melanoma, the authors recommend delaying the treatment of patients with T0 to T1 disease for 3 months if there is no macroscopic residual disease at the time of biopsy. Treatment of tumors ≥T2 can be delayed for 3 months if the biopsy margins are negative. For patients with cutaneous squamous cell carcinoma, those with Brigham and Women's Hospital T1 to T2a disease can have their treatment delayed for 2 to 3 months unless there is rapid growth, symptomatic lesions, or the patient is immunocompromised. The treatment of tumors ≥T2b should be prioritized, but a 1‐month to 2‐month delay is unlikely to worsen disease‐specific mortality. For patients with squamous cell carcinoma in situ and basal cell carcinoma, treatment can be deferred for 3 months unless the individual is highly symptomatic. Abstract : During the coronavirus disease 2019 (COVID‐19) pandemic, providers must help patients to make informed decisions regarding skin cancer management and assess the risk of potential COVID‐19–associated morbidity and/or mortality versus primary skin cancer morbidity and/or mortality. In this article, the authors summarize current data regarding the risk of COVID‐19 complications and mortality based on age and comorbidities, and review the literature assessing how treatment delays affect oncologic outcomes. They provide multidisciplinary recommendations regarding the timing of local therapy for patients with early‐stage skin cancers.